The relationship between corporate governance and audit quality: evidence from China - Zhang, Mengyuan (2020)
This paper contributes to enrich the research on the influence of corporate governance, ownership concentration and firms’ equity nature on audit quality. According to the agency theory, this study demonstrates that shareholders’ reliance on external audit is highly correlated to ownership concentration. Specifically, firms with greater ownership concentration tend to purchase extensive audit services, paying higher audit fees. Besides, the study results contribute to prior research by indicating the negatively and significantly impact of SOEs on audit quality. Moreover, with a significantly positive correlation between board diligence and audit fees, this paper also provides empirical evidence to the complementary view that governance mechanisms compensate each other, which means that firms with improved corporate governance would require for extensive audit services. In addition, the paper provides implications for regulators and policymakers that the function of the boards may be ineffective. At the same time, it also indicates that the context matters the effectiveness of the corporate governance mechanisms.